Strategi Perencanaan Pengelolaan Paud Melalui Peningkatan Kompetensi Guru di TK Tunas Harapan I Waru - Any Mariani (Departement of Mathematics Education, 2023)
Nationally, the education system in Indonesia has criteria for its management. Basically these criteria are compiled to align the quality of management in schools. However, specifically, an analysis should be carried out at each point to develop the quality of education services in the schools that organize it. This analysis should be able to help develop educational institutions to be more professional and align with the wishes of the community. Education Management has a meaning, namely a collection of activities or efforts carried out by groups of individuals to carry out a set of activities to achieve certain goals. The low skills and professionalism of teaching staff are included in the problems that have continued until now. Furthermore, there are pedagogic skills that cannot be marginalized. Pedagogic skill is an expertise in managing student learning systems, because teachers as learning staff have the function of being motivators, facilitators, engineers, learning boosters and channeling learning motivation for students. Therefore PAUD management needs to be formed to meet demand, interests, desires and determine the direction of school strategies in achieving educational goals